Application of longhole drilling methods for narrow vein mining - Peter Larsen; Richard Cyr; William Quesnel (Canadian Institute of Mining, Metallurgy and Petroleum, 1990)
"The need to continually improve efficiency and lower costs in mining operations is of paramount importance to all concerned in the industry. Mining operations are constantly testing new methods and equipment in order to lower costs and improve productivity. Equipment suppliers strive to fulfill the demands of the mines through improved design and innovative ideas for productivity increases. In some cases, however, an increase in productivity does not require new equipment design, but rather the application of an existing mining method into different operating parameters. Such is the case in applying longhole methods to narrow vein ore deposits.Bulk mining methods have long been recognized as efficient, low-cost alternatives in narrow vein operations. Typically, shrinkage and some cut-and-fill methods are employed. The shortfall of these methods is the tendency to be labour intensive. The demand for miners skilled in these methods far outweighs their availability. Consequently, labour-efficient methods have to be employed to fill the void. The application of longhole drilling techniques to narrow vein deposits is one such method.IntroductionPercussion longhole drilling evolved in Canada in the early 1940s. Prior to percussion drilling, blast holes were drilled using diamond drill equipment. Jack Gardner, of Gardner Steel, began testing with carbide percussion bits and extension drill steel in applications where diamond drills had been previously employed. Percussion drilling equipment proved to be considerably more productive and cost-efficient. The experiment eventually led to the replacement of diamond drills in this application.Over the years, the percussion methods were improved, with particular emphasis on the equipment used. Rifle bar rotation machines evolved to independent rotation. Bar and arm set ups evolved into self-contained mobile drill carriers that increased productivity while reducing the physical labour. The introduction of hydraulics further improved efficiency and production figures. Today, it is not uncommon to see fully computerized jumbos in production longhole drilling applications. These machines represent the ""state-of-the-art"" in longhole drilling equipment.Production longhole drilling is considered to be one of the most efficient bulk mining methods in use today. Production statistics normally exhibit low-cost, efficient ore extraction. As a rule, longhole (blasthole) methods are associated with substantial ore deposits. These methods have exhibited high production figures and low mining costs.Over the past decade, long hole methods have been applied to several narrow vein deposits. These applications have proven that, given the right parameters, longhole methods will produce the same advantages in narrow vein deposits as are seen in more conventional applications."